The potential of nitrate supplementation for modulating the fermentation pattern and mitigating methane emission in ruminants: A meta-analysis from in vitro experiments. Issue 1 (November 2021) - Abdelbagi, M; Ridwan, R; Nahrowi,; Jayanegara, A
Abstract: The aim of this study was to evaluate the potential of nitrate supplementation as an in vitro feed additive for modulating the rumen fermentation pattern and mitigating the enteric methane emission by using a meta-analysis method. A database was built from the previously published articles regarding the effectiveness of nitrate as a feed additive in the in vitro rumen fermentation system. Different doses or forms of nitrate supplementations were identified in the database. A total of thirteen studies containing 47 data sets were obtained from ten published research papers. The obtained data were subjected to the mixed model methodology. The doses or the different forms of nitrate were treated as a fixed factor, while the different studies were considered as a random effect. Results showed that nitrate addition decreased significantly (P<0.05) the total gas production, methane production, the TVFAs, and the acetic acid, and increased significantly (P<0.05) ammonia concentration in a linear pattern. However, nitrate did not affect significantly the rumen pH and the population of methanogenic archaea. In conclusion, nitrate is an effective additive for modulating the rumen fermentation by altering the fermentation process resulting in a lower methane production.